In vitro transdentinal effect of low-level laser therapy - Oliveira, C. F.; Basso, F. G.; Dos Reis, R. I.; Parreiras-E-Silva, L. T.; Lins, E. C.; Kurachi, C.; Hebling, J. [UNESP]; Bagnato, V S; de Souza Costa, C. A. [UNESP] (IOP Publishing, 2013)
Low-level laser therapy (LLLT) has been used for the treatment of dentinal hypersensitivity. However, the specific LLL dose and the response mechanisms of these cells to transdentinal irradiation have not yet been demonstrated. Therefore, this study evaluated the transdentinal effects of different LLL doses on stressed odontoblast-like pulp cells MDPC-23 seeded onto the pulpal side of dentin discs obtained from human third molars. The discs were placed in devices simulating in vitro pulp chambers and the whole set was placed in 24-well plates containing plain culture medium (DMEM). After 24 h incubation, the culture medium was replaced by fresh DMEM supplemented with either 5% (simulating a nutritional stress condition) or 10% fetal bovine serum (FBS). The cells were irradiated with doses of 15 and 25 J cm-2 every 24 h, totaling three applications over three consecutive days. The cells in the control groups were removed from the incubator for the same times as used in their respective experimental groups for irradiation, though without activating the laser source (sham irradiation). After 72 h of the last active or sham irradiation, the cells were evaluated with respect to succinic dehydrogenase (SDH) enzyme production (MTT assay), total protein (TP) expression, alkaline phosphatase (ALP) synthesis, reverse transcriptase polymerase chain reaction (RT-PCR) for collagen type 1 (Col-I) and ALP, and morphology (SEM). For both tests, significantly higher values were obtained for the 25 J cm-2 dose. Regarding SDH production, supplementation of the culture medium with 5% FBS provided better results. For TP and ALP expression, the 25 J cm-2 presented higher values, especially for the 5% FBS concentration (Mann-Whitney p < 0.05). Under the tested conditions, near infrared laser irradiation at 25 J cm -2 caused transdentinal biostimulation of odontoblast-like MDPC-23 cells. © 2013 Astro Ltd.
Keywords: ALkaline phosphatase; Experimental groups; Fetal bovine serum; Low level laser therapy; Near-infrared laser irradiation; Nutritional stress; Response mechanisms; Reverse-transcriptase polymerase chain reactions; Biosynthesis; Cytology; Infrared lasers; Irradiation; Laser surgery; Laser tissue interaction; Phosphatases; Polymerase chain reaction; Cells